Analysis of the bending behavior of bamboo culms with a full longitudinal crack. (15th January 2022) - Eustáquio Moreira, Luís; Seixas, Mario
Highlights: The loss of bending stiffness for bamboo culms with a full longitudinal crack was investigated through experimental, numerical and analytical models. Numerical models and Vlasov equations were used to investigate the flexural-torsion of bamboo full-culms, determining warping in bamboo tubes with open cross-sections. Finite element models were developed in good agreement with experimental models, adopting isotropy for bamboo tubes without cracks and orthotropy for bamboo tubes with cracks. Diaphragms distributed along bamboo full-culms presented a great influence to restrain warping of cracked tubes. Abstract: This paper investigates the bending stiffness of bamboo culms with and without the presence of a full longitudinal crack of the culm wall. The study aims to quantify experimentally the loss of resistance of cracked bamboo tubes in bending, in compliance with numerical modeling using the finite element method (FEM) and the classic equations of Vlasov. Experimental tests were conducted with six specimens of Phyllostachys edulis bamboo (Moso), subjected to three-point bending tests. Firstly, the samples were mechanically tested in its full-culm state without the presence of cracks and, then, with a longitudinal crack along the total lenght of the culm. The cracks were positioned in the worst-case situation, i.e., perpendicular to the bending plane. The compliance between experimental and numerical displacements measured at the center span of the samples and in FE models showed with accuracy the loss of the bending stiffness of cracked bamboo culms. The study showed that isotropic numerical models can attain the flexural properties of bamboo tubes in perfect conditions, without the presence of cracks. Although, to assess the flexural properties of bamboo tubes with the presence of a full longitudinal crack it was necessary to model the bamboo tube considering orthotropy. The numerical analysis and the Vlasov equations described with good precision the stress field in the analyzed tubes. Each sample presented a different loss of resistance, depending if the crack cut or not the diaphragms beyond the culm wall, showing a maximum loss of stiffness of 63% for cracked specimens. Thus, the results presented a significant loss of bending stiffness of cracked bamboo culms, if the culm wall cracks from one end to another, which can be considered as a damaged tube.